Germany's Secret Service Investigates the Alternative for Germany. Issue 2 (1st June 2019) - Klikauer, Thomas; Tunney, Kathleen Webb
Abstract : By the end of 2018, Germany's secret service, the Federal Office for the Protection of the Constitution (Bundesamt für Verfassungsschutz) started composing a report on Germany's most notorious right-wing political party, the Alternative for Germany (AfD). In January 2019, one of the authors asked Germany's secret service to supply this report but was told "It's secret." On 28 January 2019, a short note even noted: "We will not send the document." On the very same day, Netzpolitik.org posted the entire report online—all 436 pages of it. Netzpolitik.org stated: "We make the report available because open debate is vital in a democracy… and because it destroys the AfD's fairy-tale of being a normal political party." In their introduction, Netzpolitik's Andre Meister, Anna Biselli, and Markus Reuter, who published the report, also emphasize: "We make the report available because the secret service believes 'parts of the AfD violate Germany's constitutional guarantee that human dignity is inviolable."' Netzpolitik.org is convinced that Germans have a right to know. Reading through the report one hardly finds evidence that would justify secrecy. Instead, it is a valid report written by a German state agency tasked with defending the Basic Law (Grundgesetz) concerning a political party.